Determination of cytotoxicity and invasiveness of heterotrophic plate count bacteria isolated from drinking water - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2013)
Dissertation (MSc (Medical Virology))--University of Pretoria, 2005.